MicroRNAs as Therapeutic Targets in Nasopharyngeal Carcinoma - Wang, Sumei; Claret, François-Xavier; Wu, Wanyin (Frontiers in Oncology, 2019)
Nasopharyngeal carcinoma (NPC) is a malignancy of epithelial origin that is prone to local invasion and early distant metastasis. Although concurrent chemotherapy and radiotherapy improves the 5-year survival outcomes, persistent or recurrent disease still occurs. Therefore, novel therapeutic targets are needed for NPC patients. MicroRNAs (miRNAs) play important roles in normal cell homeostasis, and dysregulations of miRNA expression have been implicated in human cancers. In NPC, studies have revealed that miRNAs are dysregulated and involved in tumorigenesis, metastasis, invasion, resistance to chemo- and radiotherapy, and other disease- and treatment-related processes. The advantage of miRNA-based treatment approaches is that miRNAs can concurrently target multiple effectors of pathways involved in tumor cell differentiation and proliferation. Thus, miRNA-based cancer treatments, alone or combined with standard chemotherapy and/or radiotherapy, hold promise to improve treatment response and cure rates. In this review, we will summarize the dysregulation of miRNAs in NPC initiation, progression, and treatment as well as NPC-related signaling pathways, and we will discuss the potential applications of miRNAs as biomarkers and therapeutic targets in NPC patients. We conclude that miRNAs might be potential promising therapeutic targets in nasopharyngeal carcinoma.